0 кккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккккорней
<span>50-(22,95/2,7+3,4)*2,8=50-(8,5+3,4)*2,8=50-11,9*2,8=50-33,32=16,68</span>
Ответ:
Пошаговое объяснение:
приведем последнее выражение к общему знаменателю
не знаю что тут еще можно сделать
Lg(3x-y)=1--->3x-y=10
lg(x+2)+lg(x+3)=lg3+1--->lg((x+2)*(x+3)/3)=1--->(x+2)*(x+3)/3=10
ОДЗ х> -3;
3x-y=10
(x+2)(x+3)=30
x=3;y= -1
cos(x-y)=-1--->(x-y)=(2n+1)*pi
sin(x+y)=-0.5--->(x+y)=(2n-1)*pi/6
x = (7 pi*n)/6+(5*pi)/12, y = -(5 pi* n)/6-(7* pi)/12